Perception of techno-stress among university undergraduates - Adebayo M. Ishola; Owolabi P. Adelana; Olufunbi J. Akorede (Pejabat Karang Mengarang UPSI, 2022)
The field of Human-Computer Interaction (HCI) is multidisciplinary, cutting across computer science, psychology, cognitive science, and organizational and social sciences. In the social sciences, HCI tries to understand students' experiences, and resultant effects based on interaction with technology. As technology integration in education keeps rising, the need arises to examine the side effects of constant, and prolonged use of technology by students because there has been concern about how human-computer interaction, especially on devices with screens or other forms of user interfaces, influences techno-stress (technology-influenced stress) among students. This study, therefore, examined human-computer interaction and techno-stress among undergraduates. The descriptive survey of the non-experimental design was adopted, and the sample comprised 313 final-year undergraduates, to whom an instrument titled "Technology-Generated Stress Questionnaire (CGSQ)" (r = .74), was administered for data collection. Descriptive and inferential statistics of Median, S.D, T-test, and One-Way ANOVA, were used for analysis at 0.05 alpha level. Findings showed that undergraduates have positive perceptions of technology-influenced stress, and based on gender and age, no significant difference exists in their perceptions. Stakeholders need to come up with policies guiding students' interaction with technology for learning purposes to avert negative consequences on their mental well-being.